HLA-G 5′URR regulatory polymorphisms are associated with the risk of developing gliomas. (3rd April 2023) - Durmanova, Vladimira; Kluckova, Kristina; Filova, Barbora; Minarik, Gabriel; Kozak, Jan; Rychly, Boris; Svajdler, Marian; Matejcik, Viktor; Steno, Juraj; Bucova, Maria
Abstract: Background: Human leukocyte antigen G (HLA-G) belongs to non-classical MHC class I molecules that is involved in the suppression of immune response. As HLA-G plays important role in the maintenance of fetal tolerance, its overexpression has been associated with tumor progression. For the regulation of HLA-G levels, genetic variants within the 5′ upstream regulatory region (5′URR) are of crucial importance. Our study aimed to analyze the association between 16 HLA-G 5′URR variants, sHLA-G level and clinical variables in glioma patients. Methods: We investigated 59 patients with gliomas (mean age 54.70 ± 15.10 years) and 131 healthy controls (mean age 41.45 ± 9.75 years). Patient's blood was obtained on the day of surgical treatment. The HLA-G 5′URR polymorphisms were typed by direct sequencing and the plasma level of sHLA-G assessed by ELISA. Results: Haploblock within HLA-G 5′URR consisting of −762T, −716G, −689G, −666T, −633A, followed by −486C and −201A alleles were significantly more frequent in patients with gliomas than in the controls ( p  < 0.05). No correlation of HLA-G 5′URR variants with sHLA-G plasma level was found. Analysis of HLA-G 5′URR variants with main clinical variables in patients with grade IV gliomas revealed that haploblock carriers of −762CT, −716TG, −689AG, −666GT, −633GA, −486AC, −477GC, −201GA followed by −369AC carriers tend to have lower age at onset as compared to other genotype carriers ( p  = 0.04). Conclusion: Our results suggest genetic association of HLA-G 5′URR variants with risk of developing gliomas and possible contribution of HLA-G to disease pathology.